THE IMPACT OF ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) ON RETURN ON ASSETS (ROA) (Cross-Country Evidence of the Energy Sector in 2019-2021) - Andika Daffa Elianto; Erman Denny Arfinto; Nana Varian Januardi (Faculty of Economics and Business Diponegoro University, 2023)
ABSTRACT The purpose of this study is to examine how Environmental, Social, and Governance Disclosure affects business profitability. Three factors, including the environmental (ENVDiscI), social (SOCDiscI), and corporate governance (GOVDiscI) Disclosures components, are used to assess ESG disclosure. Meanwhile, Return on Assets serves as a proxy for the company's financial performance (ROA). Financial Leverage (FL) and Asset Turnover (AT) are two additional control variables used in this study. A total of 140 companies consists of energy sector enterprises in Indonesia, Germany, Finland, the United States, Brazil, India, and South Africa made up the sample for this study, which employed purposive sampling and secondary data from Bloomberg Database. Multiple linear regression analysis is used in this study’s analysis, and IBM SPSS Statistics 25 is used to handle the data. The results suggest a significant correlation between a company's disclosure practices and its ROA. Specifically, ENVDiscI and SOCDiscI demonstrated a positive and significant impact on ROA, whereas GOVDiscI negatively influenced ROA. These results suggest that prioritizing environmental and social disclosures can potentially enhance a company's Return on Assets, while an excessive emphasis on governance disclosures may be counterproductive. This study's findings underline the crucial role transparency in environmental and social practices can play in driving a company's profitability, emphasizing the need for more comprehensive ESG disclosures in shaping industry best practices.